Effectiveness Of Productive Zakat Programs In Improving The Welfare Of Mustahiq: A Study At Baznas Bone Regency - Bunga Bunga; Rini Idayanti; Shadriyah Shadriyah (Universitas Islam Darul 'ulum Lamongan, 2026)
This study analyzes the effectiveness of the productive zakat program implemented by BAZNAS Bone Regency in improving the welfare and economic independence of mustahik (recipients). Traditional zakat distribution is often consumptive, providing only temporary relief , whereas productive zakat aims to create sustainable income by providing business capital. This research used a qualitative field research design, conducted at the BAZNAS Bone office. Data was collected through in-depth interviews with BAZNAS management and mustahik, observation, and documentation. The findings prove the program is effective. Recipients, including a 'Thai Chicken Rice Bowl' culinary entrepreneur and a small shop owner, demonstrated significant economic improvement. They transitioned from unemployment or lacking capital to generating stable income, achieving economic independence, hiring employees, and funding their children's education. The study concludes that the productive zakat program effectively improves mustahik welfare. However, to optimize results and overcome identified challenges, such as marketing and financial separation, reinforcement through continuous mentorship and entrepreneurship education is necessary.